NEW DATA ON THE STRATIGRAPHY OF DEPOSITS AND HYDROGEOCHEMICAL CONDITIONS OF PRADNIEPER AREA (NORTH-WESTERN PART OF THE BLACK SEA SHELF) - Zhabina, N.; Anikeyeva, O.; Kolodiy, I.; Mintuzova, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of the reomvestogatopm study and retrospective analysis of materials of parametric drilling of the Pradniprovska-2 well are represented. Investigations of stratigraphy, microfacial and micropaleontological study of the well have been carried out. The hydrogeochemical and gas-hydrogeochemical indicators (gas composition of water dissolved gases and pressure of saturation) of oil and gas contents are also analyzed. In the studied section sediments that are treated to be Tithonian some sequence discontinuites were found and the presence of rocks containing numerous planktonic foraminiferas of the Lower and Upper Cretaceous (Albian-Cenomanian) were revealed. Additional study of the section and analysis of the stratigraphic distribution of determined does not reveale the Tithonian sediments but incicate the presence of of tectonic dislocation zone which comprizes Upper Jurassic (Tithonian, Kimmeridge–Tithonian), Upper Jurassic–Lower Cretaceous (Tithonian–Berriasian) and Cretaceous (Albian-Cenomanian) depositions. The hydrogeochemical evidences and high values of hydrostatic coeficient testify to hydrogeological isolation of the underground levels of the Pradnieper area. Water dissolved gases of hydrocarbon composition are of very informative. High relative gas saturation of the formation water from the Maikopian sediments may indicate that the well has gone out of the contour of gasbearing strata. The water inflows produced during the testing of the Lower Cretaceous deposits and hydrocarbon composition of dissolved gas may indicate the prospects of the Lower Cretaceousones. However, to obtain reliable numerical values of certain parameters during the test of water-bearing objects it is necessary to do qualitative sampling of formation water. The data on the stratigraphy and hydrogeology of deposits discovered in the Pradnieper area, indicate the necessity in prolongation of geological and exploration work on the slope of the East European Platform where besides Pradnieper uplift a group of prospecting uplifts as to hydrogeological features (Tendrivska, Dniester, Skadovsk) have been revealed and which can be usefull at planning and carrying out of exploration works.
Keywords: Upper Jurassic; Cretaceous; Maikopian; tectonic dislocation; hydrogeochemical indicators; water dissolved gases; the Black Sea oil- and -gas-bearing basin